Analysis of body composition parameters: Associations with gender, age, and adiposity indices in adults - Husain, Fareha; Mohd. Yasir Zubair; Shahnawaz Alam (Asian Journal of Medical Sciences, 2025)
Background: Height-independent body composition parameters such as fat free mass index (FFMI) and body fat mass index (BFMI) allow height-independent interpretation of nutrition status and putatively provide a better assessment of body fat. Aims and Objectives: This study was undertaken to investigate the relationships between body composition parameters and their associations with gender, age, and adiposity indices in adults using bioelectrical impedance analysis (BIA). Materials and Methods: A cross-sectional study was conducted on 120 participants (60 males, 60 females) aged 18 years and older. Body composition parameters including body mass index (BMI), BFMI, FFMI, total body water (TBW), intracellular water (ICW), and extracellular water (ECW) were measured using BIA. Participants were stratified by age and gender for comparative analyses. Results: Significant gender differences were observed across all parameters. Females showed higher BMI (26.75 vs. 24.38 kg/m2) and BFMI (9.755 vs. 5.85 kg/m2), while males demonstrated higher FFMI (17.63 vs. 16.50 kg/m2) and TBW (60.59% vs. 50.95%). Among age groups, only BMI showed significant differences (P=0.024), with the highest values in the 40–59 years group. Strong positive correlations were found between BFMI and BMI (r=0.776, P<0.01) and TBW with ICW (r=0.962, P<0.01). Strong negative correlations were observed between TBW and BFMI (r=−0.830, P<0.01). Age showed no significant correlations with any body composition parameters. Conclusions: The study demonstrates significant gender-based differences in body composition parameters and reveals that BMI correlates strongly with FM but only moderately with fat-free mass. Most body composition parameters remain relatively stable across age groups. These findings emphasize the importance of gender-specific approaches in body composition assessment and suggest the need for more comprehensive evaluation methods beyond traditional BMI measurements.